2003
DOI: 10.1177/0148558x0301800205
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory CEO Retirements, Discretionary Accruals, and Corporate Governance Mechanisms

Abstract: Prior research predicts that retiring CEOs will attempt to increase reported earnings in their final year in order to receive larger bonus payments (the short horizon hypothesis) (Murphy and Zimmerman [1993]). An alternative incentive to increase earnings in final years may come from the desire to secure lucrative post-retirement board seats. Brickley et al. (1999) find that performance in the departing CEO's final four years is positively related to: (1) the probability of the CEO retaining his or her board s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 28 publications
(51 reference statements)
3
39
0
6
Order By: Relevance
“…(2004) document that the level of audit committee independence is negatively associated with earnings management, Lin et al . (2006), Reitenga & Tearney (2003), and Xie et al . (2003) do not find such a significant relationship.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…(2004) document that the level of audit committee independence is negatively associated with earnings management, Lin et al . (2006), Reitenga & Tearney (2003), and Xie et al . (2003) do not find such a significant relationship.…”
Section: Resultsmentioning
confidence: 98%
“…However, while such expectation is easily understandable, the positive effect of audit committee independence on financial reporting quality is not consistently supported in prior studies. For example, while Klein (2002) and Abbott et al (2004) document that the level of audit committee independence is negatively associated with earnings management, Lin et al (2006), Reitenga & Tearney (2003), and Xie et al (2003) do not find such a significant relationship. The meta-analysis results reported in Table 3 show a highly significant negative relationship (at the 1% level) between AC independence and earnings management, consistent with the expected effect.…”
Section: Ac Independencementioning
confidence: 93%
“…Indeed much of the existing studies find upward earnings management prior to the outgoing CEO's departure and/or downward earnings management by the incoming CEO (Dechow and Sloan, 1991;Pourciau, 1993, Brickley et al 1999Reitenga and Tearney, 2003;Conyon and Florou, 2004). 3 Studies based on Australian data also provide evidence in support of a big bath, but there is little evidence of earnings management by the departing CEO (Wells, 2002;Godfrey et al, 2003;Wilson and Wang, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study isolated the relationship between the company's CSR performance and supply-chain CPAs (CSRSCPAs) with respect to DA. Previous studies (Wilson & Wang 2010;Conyon & Florou 2004;Reitenga & Tearney 2003;Godfrey et al 2003;Brickley et al 1999;Dechow & Sloan 1991) indicated that CEO turnover is commonly related to earnings quality. The results of these studies are listed in Panel A of Table 6, which shows that the CEO turnover rate was14.86% (334/2,284) in the sub-sample of CSRSCPA.…”
Section: Consideration Of Ceo Turnovermentioning
confidence: 98%